The Influence of Good Corporate Governance, Return on Assets and Financial Distress with Firm Size as a Moderating Variable on the Integrity of Financial Reports - Triani, Merry; Cahyowati, Anik; Andjioe, Oscar Rynandi (Eksos, 2024)
Quality financial reports are financial reports that are equipped with complete reports. To protect the rights of stakeholders. This research aims to see which is proxied by the audit committee, Return On Assets (ROA) and Financial Distress and to find out whether Firm Size is a Moderating Variable the influence of Good Corporate Governance on the Integrity of Financial Reports partially. This research uses quantitative research known as associative research. For the population, financial report data from companies in the manufacturing industry for 2018-2020 were used and a purposive sample was used. This study are multiple regression analysis and path analysis with Eviews 10 software for data analysis tools. The results of the research show that Good Corporate Governance as proxied by the audit committee, Return On Assets (ROA), and Financial Distress does not partially result the Integrity of Financial Reports, on the contrary Companies can weaken the affect of the audit committee on the integrity of financial reports and strengthen the influence ROA and financial distress on the integrity of financial reports.